Context, Existing Frameworks, and Practicality: Moving Forward with Synthetic Biology - Carter, Sarah R. (The Hastings Center report, 2014)
Synthetic biology has generated extensive discussion about a wide range of risks and potential benefits, the intrinsic value of the technology, and the societal distribution of its risks and benefits. However, before these questions can be resolved, it is important to first ask a critical question: Is synthetic biology different enough from the technologies that came before it that it raises new questions or concerns? By putting synthetic biology into context, we gain a better understanding of the issues, both old and new, that it raises. We can then consider practical governance questions, including ways to improve current practices.